Identification of Serial DNA Methylation Changes in the Blood Samples of Patients with Lung Cancer - Da Hye Moon, M.D.; Sung Ok Kwon, Ph.D.; Woo Jin Kim, M.D.; Yoonki Hong, M.D. (Tuberculosis and Respiratory Diseases, 2019)
Background The development of lung cancer results from the interaction between genetic mutations and dynamic epigenetic alterations, although the exact mechanisms are not completely understood. Changes in DNA methylation may be a promising biomarker for early detection and prognosis of lung cancer. We evaluated the serial changes in genome-wide DNA methylation patterns in blood samples of lung cancer patients.